2021
DOI: 10.3389/fevo.2021.657755
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Assembly, Adaptive Strategies and Positive Interactions During Primary Succession in the Forefield of the Last Venezuelan Glacier

Abstract: Glaciers are receding at unprecedented rates in the alpine tropics, opening-up new areas for ecosystem assembly. However, little is known about the patterns/mechanisms of primary succession during the last stages of glacier retreat in tropical mountains. Our aim was to analyze soil development and vegetation assembly during primary succession, and the role of changing adaptive strategies and facilitative interactions on these processes at the forefront of the last Venezuelan glacier (Humboldt Peak, 4,940 m asl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
3
14
0
1
Order By: Relevance
“…Recently deglaciated terrains are harsh environments as vegetation is sparse, they are nutrient poor, and they often are isolated and di cult to reach. It has been demonstrated that succession in those harsh environments is primarily dominated by a gradual addition of species during ecosystem development 16,17 , while replacement is often hypothesized to be weak or absent in harsh environments 2,12,14 . Still, it is possible that the relative importance of species addition versus replacement changes through time, and the short time window covered by the studies could have overemphasized the importance of addition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently deglaciated terrains are harsh environments as vegetation is sparse, they are nutrient poor, and they often are isolated and di cult to reach. It has been demonstrated that succession in those harsh environments is primarily dominated by a gradual addition of species during ecosystem development 16,17 , while replacement is often hypothesized to be weak or absent in harsh environments 2,12,14 . Still, it is possible that the relative importance of species addition versus replacement changes through time, and the short time window covered by the studies could have overemphasized the importance of addition.…”
Section: Introductionmentioning
confidence: 99%
“…3b). Most studies included solar radiation (n = 11) (e.g., Caccianiga and Andreis, 2004;D'Amico et al, 2017;Fickert, 2020;Lambert et al, 2020), years since deglaciation (n = 43) (e.g., Fickert and Grüninger, 2018;Jiang et al, 2018;Franzén et al, 2019;Knoflach et al, 2021;Wei et al, 2021), soil moisture (n = 9) (e.g., Matthews and Whittaker, 1987;Andreis et al, 2001;Raffl and Erschbamer, 2004;Szymański et al, 2019;Fickert, 2020), elevation (n = 22) (e.g., Carlson et al, 2014;Schumann et al, 2016;Llambí et al, 2021;Wei et al, 2021), inclination (n = 15) (e.g., D'Amico et al, 2017;Haselberger et al, 2021;Wietrzyk-Pelka et al, 2021), aspect (n = 14) (e.g., Caccianiga and Andreis, 2004;Raffl and Erschbamer, 2004;Fickert, 2017;Lambert et al, 2020;Wietrzyk-Pelka et al, 2021), and disturbance (n = 9) (e.g., Matthews and Whittaker, 1987;Andreis et al, 2001;Eichel, 2019) as well as soil-related parameters such as organic carbon (n = 16) (e.g., D'Amico et al, 2014;Jiang et al, 2018;Wietrzyk et al, 2018;Losapio et al, 2021), nitrogen (n = 14) (e.g., Raffl et al, 2006;Burga et al, 2010;Fickert, 2020;Wei et al, 2021), and pH (n ...…”
Section: Literature Review: Definition Of the Dependent And Potential...mentioning
confidence: 99%
“…For total vegetation cover we hypothesised that the most important drivers influencing the development in the proglacial area are: years since deglaciation, elevation, and climatic variables. This hypothesis was based on previous studies in which years since deglaciation (e.g., Matthews and Whittaker, 1987;Raffl et al, 2006;Erschbamer and Caccianiga, 2016;Schumann et al, 2016;Llambí et al, 2021), elevation (e.g., Raffl and Erschbamer, 2004;Lambert et al, 2020), temperature (e.g., Fickert et al, 2017;Franzén et al, 2019;Fickert, 2020), and precipitation (e.g., Schumann et al, 2016;Haselberger et al, 2021) resulted as essential drivers of vegetation development. In our study, we have now demonstrated thatcontrary to our initial expectationa series of other variables correlates with our hypothesised three variables, jointly described by the components RC1 ('elevation and time'), RC2 ('solar radiation'), RC3 ('south-eastness'), and RC5 '(low inclination').…”
Section: Drivers For Development Of Vegetation Covermentioning
confidence: 99%
“…For mountain plant species this lag has been split into three types: dispersal lag, establishment lag and extinction lag (Alexander et al 2018). In the upper alpine zone, where upward migration is assimilated to a primary succession on mostly abiotic terrains (Walker and Del Moral 2003), this lag has been associated with dispersal limitation (dispersal lag) and a deficit in positive interactions between plants (establishment lag; Zimmer et al 2018;Llambí et al 2021). Nevertheless, the very slow development of alpine soils, especially the slow enrichment in organic matter (Khedim et al 2021) means that, even if plants are capable of reaching upward sites, they may not be able to establish because of the lack of organic matter (establishment lag).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying species' losses and gains is a topical challenge given the high pace of climate warming in this region, which belongs to one of the major hotspots of vascular plant biodiversity in the world: the Tropical Andes (Mittermeier et al 2011;Peyre 2021). From a functional viewpoint, the few studies examining the first decades of plant primary succession after glacial retreat in the alpine tropics evidenced significant changes in species strategies (e.g., from opportunistic to stress tolerant; Zimmer et al 2018;Rosero et al 2021) and in growth forms (Llambí et al 2021). This said, the absence of pronounced seasonality and seasonal snowpack as well as the decreasing precipitation at higher elevations in tropical alpine environments have been suggested to result in different functional trait values in the tropics and in temperate-arctic environments (Cruz-Maldonado et al 2021).…”
Section: Introductionmentioning
confidence: 99%